A Case of Acute Gonococcal Conjunctivitis in an Unusual Age Group - Rana, Rachana Singh; Gurung, Reeta (Nepalese Journal of Ophthalmology, 2021)
Introduction: This is a case of case of acute gonococcal conjunctivitis in a 2.5 years old female child. Case: A 2.5 years old female child presented with redness, purulent and profuse discharge from left eye with associated upper eyelid swelling. The culture of conjunctival swab revealed Neisseria gonorrhoeae. The child was treated with intravenous antibiotics and fortified medications. Conclusion: Unlike young adults and newborn gonococcal conjunctivitis (GCC), children can have a nonsexual mode of transmission and could be seen in an unusual age group. For the management of the diseases, proper history including sexual abuse history and thorough physical examination is mandatory, which is sometimes difficult in a developing country. Gonococcal conjunctivitis in the toddler group should be kept in consideration.